Method for multi-mycotoxin analysis in Indian medicinal herbs - Sarkar, Rohan; Banerjee, Kaushik (Indian Horticulture, 2023)
Although medicinal plants are in huge demand across the world for their health promoting effects, they can pose potential health concern to consumers if contaminated with mycotoxins. That’s why a standardized method is of utmost importance to analyse these contaminants in medicinal plant matrices. The unavailability of such standardised methods for analysing multiclass mycotoxin was realized and a process was optimized following a single chromatographic run but with lower LOQs with desired selectivity and sensitivity from consumer safety point of view. This study reports a method to estimate nine regulated mycotoxins in a range of Indian medicinal plants including giloy (Tinospora cordifolia), ashwagandha (Withania somnifera), safed musli (Chlorophytum borivilianum),satavari (Asparagus racemosus) and tulsi (Ocimum sanctum).